University internal organization and scientific research: historical remarks - Szymaniec , Piotr (Prawo Kanoniczne, 2024)
Universities are a special institution that appeared in Western civilization in the Middle Ages. However, it was not until the 19th century that universities became the basic and main places of development of science. The essay presents the factors that led to this state of situation. Particular emphasis is placed on institutional factors, especially the internal organization of the university. The essay asks the question what historically shaped solutions in the structure and internal organization of the university were most conducive to the development of scientific research. Historical examples used in the work show that universities develop dynamically if the organization of universities ensures not only formal autonomy (as is the case in the Humboldt model of the university), but also motivates scientific development and building one’s own position by individual scholars.